RADICALISM AND MODERNITY - RAKUSA-SUSZCZEWSKI, Mikołaj (Studia Universitatis Babes-Bolyai Studia Europaea, 2017)
In contemporary debates on social radicalism there is a predominant belief that it carries with it serious threats to the public sphere, similar to all manifestations of extremism and other attitudes that challenge and question the liberal basis of the social order. The persistent and almost obsessive identification of radicalism with populism and religious fundamentalism, and in general with danger to the social order, seems to confirm this tendency. Meanwhile, the alternative subject literature indicates how much this way of thinking is ideologized and aligned with conservatism in thought, casting a blind eye to the complex motives of the radical subject. We refer here to various applications of radicalism as a philosophical, psychological and social predicament, which prompts the revision of abusive and simplified interpretations. We also assume that radicalism, as properly understood, can be interpreted as a kind of peculiar fever emerging out of the piling up of possibilities brought about by modernity. Radicalism is a disquieting state of mind, which appears not so strongly in a risk society as in a society of infinite opportunities.